1985
DOI: 10.1029/jc090ic01p00869
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for wind‐pumping of air‐sea gas exchange based on direct measurements of CO2 fluxes

Abstract: In a series of measurements of CO2 flux over the sea the mean flux was near zero, even though the surface water had substantially higher partial pressure of CO2 than the air. Hourly variations in wind speed were well correlated with the flux, suggesting that a wind‐driven process, such as wave breaking and downward mixing of bubbles, may drive additional CO2 into the water as the wind speed increases. The traditional model of air‐sea gas flux as a function of sea‐air partial pressure difference was modified to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…They concluded that the upward flux of carbon dioxide was attributable to seasonal warming with an associated reduction in the carbon dioxide solubility and an increase of the partial pressure of carbon dioxide in the sea water. Smith and Jones (1985) duplicated experiments at the same place in late autumn. Wesely el al.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the upward flux of carbon dioxide was attributable to seasonal warming with an associated reduction in the carbon dioxide solubility and an increase of the partial pressure of carbon dioxide in the sea water. Smith and Jones (1985) duplicated experiments at the same place in late autumn. Wesely el al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, eddy correlation measurements of CO2 eddy flux were made over shallow coastal water (Jones and Smith, 1977;Wesely et al, 1982;Smith and Jones, 1985). It is interesting to note that the CO2 is transported upward over the sea water during summer months, and that upward fluxes are nearly proportional to friction velocity u*.…”
Section: Co2 Flux Over Sea Watermentioning
confidence: 99%
“…They concluded that the upward flux of CO2 was attributed to seasonal warming with an associated reduction in the CO2 solubility and an increase of the partial pressure of CO2 in the surface water. Smith and Jones (1985) duplicated experiments at the same place in late autumn to see the downward flux of CO2. Wesely et al (1982) measured the CO2 flux with the eddy correlation technique over the sea off the coast of Florida during a period of increasing sea surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As a minimum, reasonably accurate probability density functions should be used to calculate the average exchange coefficient, < E >. Beginning over a decade ago, turbulence measurements of CO 2 have developed slowly [91, [12], [17], [26] and generated sharp controversy. To the extent that they have been compared, the turbulent results exceed the bulk fluxes by factors of 5 to 10.…”
Section: Liss and Merlivat [11]mentioning
confidence: 99%